Some aspects of oncology - Heppner, Gloria H.; Bittar, E. Edward; ScienceDirect eBooks (Greenwich, Conn. : Jai Press, 1996)
The present volume is the first in the advances in oncobiology series. It is meant to be useful not only to clinical and non-clinical oncologists but also to graduate students and medical students. The individual chapters are presented as self-contained summaries of current knowledge rather than as reviews. The last chapter deals with the subject of chemotherapy.
Vol. 3 The Oncobiology of the Prostate.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Cancer; Oncology; MEDICAL -- Oncology; HEALTH & FITNESS -- Diseases -- Cancer; Cancer; Oncology; Neoplasms -- etiology; Neoplasms -- pathology; Neoplasms -- therapy; Electronic books